Radiation Resistance in KRAS-Mutated Lung Cancer Is Enabled by Stem-like Properties Mediated by an Osteopontin–EGFR Pathway - Wang, Meng; Han, Jing; Marcar, Lynnette; Black, Josh; Liu, Qi; Li, Xiangyong; Nagulapalli, Kshithija; Sequist, Lecia V.; Mak, Raymond H.; Benes, Cyril H.; Hong, Theodore S.; Gurtner, Kristin; et al. (Cancer research (Chicago, Ill.), 2017)
Lung cancers with activating KRAS mutations are characterized by treatment resistance and poor prognosis. In particular, the basis for their resistance to radiation therapy is poorly understood. Here, we describe a radiation resistance phenotype conferred by a stem-like subpopulation characterized by mitosis-like condensed chromatin (MLCC), high CD133 expression, invasive potential, and tumor-initiating properties. Mechanistic investigations defined a pathway involving osteopontin and the EGFR in promoting this phenotype. Osteopontin/EGFR–dependent MLCC protected cells against radiation-induced DNA double-strand breaks and repressed putative negative regulators of stem-like properties, such as CRMP1 and BIM. The MLCC-positive phenotype defined a subset of KRAS-mutated lung cancers that were enriched for co-occurring genomic alterations in TP53 and CDKN2A. Our results illuminate the basis for the radiation resistance of KRAS-mutated lung cancers, with possible implications for prognostic and therapeutic strategies. Cancer Res; 77(8); 2018–28. ©2017 AACR.